THE SOCIO-ECONOMIC REALITY OF BEING A DAY LABOURER IN PRETORIA1 - Blaauw, Derick; Pretorius, Anmar; Louw, Huma; Schenck, Rinie (Social Work/Maatskaplike Werk, 2007)
Day labourers are workers who wait on street corners or in other public places for opportunities to work. They are individuals who work for different employers and get paid on a daily basis. Because they are excluded from the formal labour market, these workers often work for different employers each day, are paid in cash, and do not enjoy benefits such as health insurance and unemployment benefits. It is mainly the employers who benefit from this relationship. They do not have many commitments towards these workers and use them only when work is available.